OPPORTUNITIES FOR THE USE OF INNOVATIONS AND ARTIFICIAL INTELLIGENCE IN PRESCHOOL EDUCATION (Journal of Universal Science Research, 2026)
The rapid development of digital technologies has brought new possibilities to preschool education, encouraging educators to reconsider traditional approaches to early learning. Innovations and artificial intelligence (AI) are increasingly being used to enrich childrenʼs learning experiences, offer personalized instruction, and support holistic development. AI-based tools enable teachers to track individual progress more accurately, identify learning needs at an early stage, and design interactive activities that promote cognitive, social, and emotional growth. Digital innovations also help create adaptive learning environments that accommodate diverse learning styles, making early education more inclusive and effective. This paper discusses potential benefits, practical applications, and challenges related to the integration of innovations and AI in preschool settings, offering insights for educators, policymakers, and researchers interested in advancing early childhood education.